Pengaruh Status Sosial Ekonomi dan Penggunaan Smartphone Terhadap Motivasi Belajar Siswa Kelas X dan XI Kuliner SMK Negeri 1 Salatiga - Budhiyanti, Katrin; Saptariana, Saptariana; Wahyuningsih, Wahyuningsih (LPPM Universitas Negeri Jakarta, 2025)
Learning motivation is an incentive that causes learning activities so that the goal is achieved. Socioeconomic status and smartphone usage are external factors that affect learning motivation. The condition of the lower middle to dominant socioeconomic status and students who use smartphones excessively in class X and XI Culinary SMK Negeri 1 Salatiga, therefore the purpose of this study is to find out the condition of socioeconomic status, smartphone use, and learning motivation as well as the influence of socioeconomic status and smartphone use on the learning motivation of class X and XI Culinary SMK Negeri 1 Salatiga. The research method is quantitative with questionnaire data collection techniques. The questionnaire will be tested for validity and reliability, descriptive percentage, classical assumption, and hypothesis test. The results of the analysis showed that there was an effect of socio-economic status on student learning motivation of 12.8%, there was an effect of smartphone use on student learning motivation of 3.8%, and there was an effect of socioeconomic status and smartphone use on learning motivation of 19,9%. The conclusion of the study is that the condition of low socioeconomic status is 60.9%, high smartphone usage is 50.5%, high learning motivation is 93.3%, the effect of socioeconomic status on learning motivation, the effect of smartphone use on learning motivation, and the effect of socioeconomic status and smartphone use on motivation. Research suggestions are that teachers are expected to support students' learning motivation, schools are expected to make policies for the use of smartphones and provide scholarships, parents are expected to monitor students' smartphone use and motivate learning, students are expected to be consistent in using smartphones wisely and increase learning motivation, and researchers are next expected to add other factors that affect learning motivation.